Anterior Scleritis Associated with Pemphigus Vulgaris. (3rd April 2019) - Zeeli, Tal; Bar-Ilan, Efrat; Habot-Wilner, Zohar; Sprecher, Eli
ABSTRACT: We present a rare co-occurrence of anterior scleritis developing in a patient with recalcitrant pemphigus vulgaris. We discuss the clinical and therapeutic implications of these two conditions and offer concise recommendations.